F-Approximately Regular Modules - Mawlood, Ahmed K.; Al-Mothafar, Nuhad Salim (Iraqi Journal of Science, 2022)
We introduce in this paper the concept of an approximately pure submodule as a     generalization of a pure submodule, that is defined by Anderson and Fuller. If every submodule of an R-module  is approximately pure, then  is called F-approximately regular. Further, many results about this concept are given.